Pengaruh Minuman Kombinasi Semangka (Citrullus lanatus) dan Air Kelapa (Cocos Nucifera L) terhadap Kecepatan dan Power Lari Atlet Taekwondo Remaja - Hadi, Risa; Harun, Harun; Ahmad Sahedi, Romadhon (Indonesian Journal of Physical Education and Sport Science, 2024)
Study purpose. This study aims to evaluate the effect of watermelon (Citrullus lanatus) and coconut water (Cocos nucifera L) combination juice on 10m sprint speed and long jump power in adolescent male Taekwondo athletes at Al-Islam Beber Islamic Boarding School. Materials and methods. The method used was an experiment where 20 athletes aged 14 ± 0.81 years were divided into 2 groups, 10 athletes were given a combination of watermelon juice and coconut water and 10 other athletes were given plain water as a control. Both groups performed taekwondo training in the form of technical and physical training for 1 hour. Before the training and after both groups performed a 10 m sprint and standing long jump. Results. The results showed that the administration of the juice did not produce significant improvements in the 10m sprint with a value of P = 0.365 (P>0.05) and long jump with a value of P = 0.234 (P>0.05), so there was no statistically significant difference between the treatment and control groups. Conclusions. Giving a combination of coconut water and watermelon juice positively improved standing long jump performance but was not statistically significant.